Comparison study between POFA and POCP in terms of chemical composition and physical properties - review paper - Hamada, Hussein M.; Fadzil, Mat Yahaya; Khairunisa, Muthusamy; Humada, Ali Mahmood (IOP Publishing Ltd., 2019)
High volume waste from agriculture industry can be utilized in concrete production instead of causing environmental problems. Palm oil fuel ash POFA and palm oil clinker powder POCP are two agricultural wastes resulted from palm oil industry. The high content of silica oxide SiO2 in the POFA and POCP are responsible for pozzolanic reaction required to improve the hydration products in the concrete mixture. However, both of POFA and POCP can be used as greener cement due to the small particle size and high surface area required to improve the mechanical properties of concrete. In addition to reduce the environmental problems due to accumulate the agriculture waste in landfills and open area.